Microbial Quality Evaluation of Seafood Samples from the Vishakhapatnam Coast, Andhra Pradesh, India - , D. Bhuvaneswari, B. Koteswar, A. Devivaraprasad Reddy, Jitender Kumar Jakhar, Rujuta R. Donadkar, CH. Balakrishna, T. Vijaya Nirmala (Archives of Current Research International, 2023)
Consumption of seafood has increased, resulting in the production and productivity of aquaculture in the past few years. Since, seafood is crucial in human nutrition, providing essential nutrients and proteins. However, their perishable nature and vulnerability to microbial contamination make them prone to spoilage and foodborne illnesses. Therefore, the microbiological analysis of fish samples is paramount to ensure their quality and safety for consumption. In this study, microbiology of fish samples, encompassing various aspects such as microbial load assessment, and pathogen detection. Isolation and identification of pathogenic bacteria viz., Total plate count, Escherichia coli, Total coliforms, Vibrio spp, Staphylococcus aureus, and Salmonella spp. These pathogens pose severe health risks to consumers and highlight the necessity of effective monitoring and control measures throughout the seafood supply chain. Proper handling, storage, and processing practices minimise microbial contamination and preserve fish quality. Implementing Hazard Analysis Critical Control Point (HACCP) plans and Good Manufacturing Practices (GMP) helps ensure the safety of fish products and prevent outbreaks of foodborne illnesses.